Role of AhR in positive regulation of cell proliferation and survival. (14th August 2016) - Yin, Jiuheng; Sheng, Baifa; Qiu, Yuan; Yang, Kunqiu; Xiao, Weidong; Yang, Hua
Abstract: The aryl hydrocarbon receptor (AhR) is an important nuclear transcription factor that is best known for mediating toxic responses by adjusting numbers of metabolism‐related enzymes, including CYP1A1 and CYP1B1. Previous findings have revealed that, in addition to negatively regulating cell proliferation and survival, AhR may also positively regulate these pathways. Here, we review these findings and summarize distinct mechanisms by which AhR promotes cell proliferation and survival, including modulation of receptor expression, growth factor signalling and apoptosis, regulating the cell cycle and promoting cytokine expression. This review will aid better understanding the role of AhR in positive regulation of cell proliferation and survival.